Accelerated Life Test and Life Analysis of Self-lubricating Radial Spherical Plain Bearing - Lu Jianjun; Qiu Ming; Li Yingchun (Jixie chuandong)
With life testing machine developed on our own,according to data terminated life test method without substitution,the accelerated life tests for a certain type of self- lubricating radial spherical plain bearing are carried out. The best linear unbiased estimation method is used to deal with test data,the accelerated life equations and the life distributions regularities are deduced. The results show that under the same work conditions,the highest life occurred under swivel motion,followed by tilt motion,and the shortest life occurred under combined swivel and tilt motion（ combined motion）. When the oscillation frequency is lower,the service lives are closer between swivel motion and tilt motion. When the oscillation frequency is higher,the service lives are closer between combined motion and tilt motion. The large differences exist among theoretical results and experimental results.